Incidence of Newborns with Down Syndrome and Factors Associated with Their Length of Hospital Stay in Hospital Pakar Universiti Sains Malaysia - Muhammad Zain, Muhammad Zul Hilmi; Nasir, Ariffin; Yaacob, Najib Majdi; Ibrahim, Nor Rosidah (Malaysian Journal of Medical Sciences, 2025)
Background: Down syndrome (DS) is the most common chromosomal disorder worldwide. This study aimed to analyse the incidence of newborns with DS in a tertiary centre in the East Coast of Peninsular Malaysia and determine the factors associated with the length of hospital stay among them.Methods: This is a retrospective study from 2017 to 2021 that recruited 41 newborns with DS. We analysed patients’ clinical characteristics, comorbidities and length of hospital stay. Kaplan-Meier survival and Cox regression analyses were used to determine the median length of hospital stay and factors affecting the length of hospital stay.Results: The incidences of newborns with DS for five consecutive years were between 0.52 and 1.39 in 1,000 live births. The gender was equally distributed and the majority were delivered from advanced maternal age with multiple antenatal histories. The majority had non-disjunction trisomy 21 and were born with multiple comorbidities. Median length of hospital stay (IQR) among newborns with DS is 24 days (17.7–30.3). Every newborn with pulmonary hypertension (adjusted hazard ratio [aHR]: 0.24; 95% CI 0.10, 0.58), feeding intolerance (aHR: 0.16, [95% CI 0.06, 0.54]) and who had been invasively ventilated (aHR: 0.13, [95% CI 0.03, 0.48]) is expected to have a prolonged hospital stay.Conclusion: The incidence of newborns with DS in Hospital Pakar Universiti Sains Malaysia is lower than other countries worldwide. We found that pulmonary hypertension, history of invasive ventilation and feeding intolerance are the main factors that affect the length of hospital stay for newborns with DS in our hospital.